Bilateral vertebral artery occlusion following cervical spine trauma -: Case report - Özveren, F; Ziyal, IM; Bejjani, GK; Yaymaci, Y; Bilge, T (Japan Neurosurgical Soc, 1999)
A 41-year-old female presented with a rare case of bilateral vertebral artery occlusion following C5-6 cervical spine subluxation after a fall of 30 feet. Digital subtraction angiography showed occlusion of the bilateral vertebral arteries. Unlocking of the facet joint, posterior wiring with iliac crest grafting, and anterior fusion were performed. The patient died on the 3rd day after the operation. This type of injury has a grim prognosis with less than a third of the patients achieving a good outcome.
Keywords: cervical subluxation; bilateral vertebral artery occlusion; vertebral artery angiography; stroke